A Computationally Inexpensive Battery Model for the Microscopic Simulation of Electric Vehicles - Schellenberg, Sebastian; Berndt, Rüdiger; Eckhoff, David; German, Reinhard (80th IEEE Vehicular Technology Conference Fall (VTC 2014-Fall), 2014)
The transition from classic combustion engine vehicles to electric vehicles is a major step to reduce worldwide CO2 emissions. In order to correctly and efficiently investigate impacts on the electric grid and the dimensioning of charging infrastructure, or to explore new technologies for a further increase of the driving range, realistic simulation models are required. In this paper, we present an accurate yet computationally inexpensive battery and kinematic model to be used in microscopic traffic simulation to help study the performance of thousands of electric vehicles. Our model also supports recuperation and range extender modules while only relying on the vehicle's speed and a set of constant predefined parameters. It can therefore be easily coupled with current sophisticated traffic simulators. We show its applicability and correctness regarding the State of Charge and power flows using comprehensive real-life experiments.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.acompu
Keywords: Electromobility; IVC; lithium-ion battery model

A Lightweight Simulation Framework for the Analysis of Electrified Vehicle Fleets - Berndt, Rüdiger; Schellenberg, Sebastian; Eckhoff, David; German, Reinhard (81th IEEE Vehicular Technology Conference Spring (VTC 2015-Spring), 2015)
Replacing combustion vehicles with electric vehicles is a major step towards reducing CO 2 emissions. With regard to this shift, in particular commercial or governmental vehicle fleets are believed to be early adopters. However, the electrification of vehicle fleets is a complex task since it can have a huge impact on companies’ day-to-day-business. This article presents a lightweight simulation framework to support the planning process and to study important effects of vehicle fleet electrification. Our discrete event-based approach allows to investigate economical and environmental aspects, such as the impact on operating costs, the required electric energy, or the amount of CO 2 emissions. Based on a given trip schedule (consisting of start time, distance, and duration), the framework allows deriving all necessary information, among others to dimension both the vehicle fleet and the charging infrastructure. We show the usefulness and the capability of our model by presenting results for a mid-sized company’s vehicle fleet comprising 100 vehicles.
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD7.alight
Keywords: Electromobility; Discrete Event-based Simulation

Alternative Approaches of Convolution within Network Calculus - Klehmet, Ulrich; Berndt, Rüdiger (Journal of Applied Mathematics and Physics, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD7.altern

An Energy Demand Model for the Microscopic Simulation of Plug-In-Hybrid Vehicles - Ammon, Lorenz; Huber, Bernd; Hübler, Florian; Berndt, Rüdiger; Schellenberg, Sebastian; Schneider, Vitali (Proceedings of the 2016 IEEE Transportation Electrification Conference and Expo (ITEC 2016), 2016)
More and more car manufactures are combining a normal combustion engine and an electric motor to satisfy the standards for CO2 emissions. In order to take advantage of this technology in the most efficient way, for example in companies car fleets, realistic simulation models are required. In this paper, we present an accurate yet computationally inexpensive energy demand model for the microscopic simulation of plug-in hybrid vehicles. Our model mostly consists of a combustion engine, an electric motor and, most importantly, a realistic engine management model. Furthermore, a pragmatic kinematic model as well as a model for recuperation of energy while breaking are provided. Modularly designed, our simulation model allows for simple replacement and adjustment of each module. As input values, our model only requires the vehicle's speed and a set of constant predefined parameters. Consequently, this also enables the model to be easily connected with current sophisticated traffic simulators. We show the correctness of our model regarding the consumption of fuel and electric energy using comprehensive real-world experiments.
Keywords: Mathematical model; Object oriented modeling; Electromobility; Plug-in Hybrid Electric Vehicle; Simulation

Construction Methods for MDD-based State Space Representations of Unstructured Systems - Berndt, Rüdiger; Bazan, Peter; Hielscher, Kai-Steffen; German, Reinhard (Proceedings of the 17th International GI/ITG Conference on "Measurement, Modelling and Evaluation of Computing Systems and "Dependability and Fault-Tolerance, 2014)
Multi-valued Decision Diagrams (MDDs) are used in various fields of application. In performance evaluation, a compact representation of the state space of Markovian systems can often be achieved by using MDDs. It is well known that the size of the resulting MDD representation heavily depends on the variable ordering, i.e. the arrangement of the levels within the MDD. Markov models, derived from higher level descriptions of the system, often contain structural information. This information might give hints for an optimized variable ordering a priori, i.e. before the MDD is constructed. Whenever a model is described by constraints-considering the design space of a system, for example-there is a lack of such structural information. This is the reason why the MDD representation often consumes too much memory to be handled efficiently. In order to keep the memory consumption practicable, we have developed two optimization mechanisms. The presented examples demonstrate that efficient MDD representations of the feasible design space can be obtained, even for large unstructured systems. © 2014 Springer International Publishing.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.constr
Keywords: Constraint computation sequence; Design space; Multi-valued decision diagram; Unstructured systems; Variable ordering

Decision Diagrams for the Verification of Consistency in Automotive Product Data - Berndt, Rüdiger (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)
The automotive manufacturing domain of these days is faced with several challenges. According to Maslow's hierarchy of needs (American psychologist, 1908-1970), the desire for individuality will steadily increase along with the growing prosperity of people. This is why the concept of mass customization has been evolving since the 1990s, i.e. "producing goods and services to meet individual customer’s needs with near mass production efficiency". Adding to this comes the progressing globalization which involves new competitors and saturated markets, especially in Europe and Northern America. In turn, car manufacturers have not only continuously developed their product range but also reduced the time to market (TTM). To achieve this, the simultaneous engineering (SE) paradigm for the development cycles of cars was adopted. On that score, well-performing flows of information are considered to be among the fundamental prerequisites. In order to implement them, a high degree of standardization is required. As a side effect, many companies struggling for markets suffered a loss of flexibility—but flexibility is essential to efficiently react to both rapidly changing framework conditions and the fast technological progress. The multitude of different concepts established by various business units is usually reflected by a high complexity within the underlying data structure. Due to this and the limited technical options regarding the design of information technology (IT) systems that prevailed in the past, in many cases a truly diverse and interlaced system topology has been evolving. While the flows of information keep getting more complex and non- transparent, the consolidation of IT system architecture is becoming ever more difficult. Nevertheless, the interdependence of business processes and IT systems is continuously growing as well. As a result, the influence of data w.r.t. decision-making and process coordination is steadily rising, thus leading to a new relevance of data quality (DQ). This is why diverse methods and management approaches to ensure high DQ were developed. But due to the application-oriented nature of many DQ problems, these methods often remained abstract and theoretical. Faced with these circumstances, the AUDI AG started a project to replace the paper- based human-machine interfaces (HMIs) controlling the assembly process of cars by an IT system. Its big advantage is given by the reduction of complexity for the operators. Still a problem is that the new system heavily relies on correct input data. Being aware of that, the AUDI AG established this doctoral research study to ensure high quality of the involved data. In the course of this thesis, a new technique is introduced focusing on the verification of consistency within the different data sources. For this, a formal model of the data including a set of consistency requirements will be developed. Based on that, multi-valued decision diagrams (MDDs) will be deployed, on the one hand to encode large sets of configurations (also: customer orders), and, on the other hand, to efficiently carry out set operations which are the basis for the verification process. The verification method requires an MDD-based representation of the feasible design space, i.e. the set of all valid configurations. But the compilation of the configuration problems of highly customizable cars leads to high memory consumption—determined by the number of nodes. The latter, in turn, can be influenced by the variable ordering, i.e. the arrangement of levels within the diagram. Therefore, both well-known and new variable ordering approaches will be applied to keep the size of the MDDs practicable. In addition to that, during the compilation of the configuration problems, the sequence of processing the constraints determines the dynamics of memory consumption. In order to keep the growth of memory consumption low, two new algorithms will be introduced. It will be demonstrated that the combined application of the presented methods allows to construct the MDD representation of the feasible design space of all investigated products. The results of the MDD-based verification technique will be validated by using a SAT- based technique (from 'Boolean satisfiability problem') which also allows to compare the performance of both approaches.<br
UnivIS-Import:2016-07-26:Pub.2016.tech.IMMD.IMMD7.decisi

Der Weg ist das Ziel - Fahrplan zur Entdeckung von datenqualitätsgefährdenden Ursachen - Berndt, Rüdiger; Blechinger, Juliane (Wirtschaftsinformatik & Management, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IMMD.IMMD6.derweg

Evaluating the Electrification of Vehicle Fleets Using the Veins Framework - Schellenberg, Sebastian; Berndt, Rüdiger; German, Reinhard; Eckhoff, David (Proceedings of the 1st OMNeT++ Community Summit 2014, 2014)
The simulative performance evaluation of future Intelligent Transport Systems (ITSs) is a challenging task. New mobility patterns, induced by car sharing or autonomous vehicles, the switch towards electric or hydrogen vehicles, and the communication between vehicles (and infrastructure) are believed to change road traffic as we know it. Investigating new applications and protocols, or finding answers to strategic questions—like the optimal placement of charging infrastructure—is often done by means of simulation. The biggest challenge is the development of realistic models that are required for these simulations in order to produce meaningful results. The case study discussed in this paper involves a company maintaining a vehicle fleet of one hundred vehicles. In this article we will discuss how we extend and deploy the Veins framework, which couples OMNeT++ and SUMO, to help in the process of electrifying this vehicle fleet, i.e., replacing combustion engine cars with electric vehicles to save money and lower CO 2 emissions.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.evalua_5
Keywords: E-Mobility; Simulation; IVC

How Electric Vehicles Can Benefit from Vehicular Networking - Schellenberg, Sebastian; Berndt, Rüdiger; Eckhoff, David; German, Reinhard (3rd GI/ITG KuVS Fachgespräch Inter-Vehicle Communication (FG-IVC 2013), 2015)
Wireless exchange of information between vehicles or vehicles and infrastructure nodes is believed to both improve traffic safety and traffic efficiency. Another trend that can currently be observed is a growing market share of electric vehicles. Unfortunately, electric vehicles still suffer from limited driving ranges and long charging times. In this paper, we not only show possible applications to alleviate these problems by the help of wireless communication but also point to models and tools necessary for their evaluation. We especially discuss how – when a vehicle is aware of its surroundings and able to predict the behavior of other vehicles or traffic lights – it can potentially optimize the process of recuperation, that is, the charging of the battery when braking. Furthermore, we show that vehicular communication can be beneficial to optimize charging strategies or job dispatching in vehicle fleets.
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD7.howele
Keywords: Electromobility; Vehicular Communication; Discrete-Event Simulation

MDD-based Verification of Car Manufacturing Data - Berndt, Rüdiger; Bazan, Peter; Hielscher, Kai-Steffen (Third International Conference on Computational Intelligence, Modelling & Simulation (IEEE), 2011)
In order to satisfy the growing demand for individualization within the automotive sector, the concept of mass customization has been continuously evolving over the past years. As a consequence, the complexity within the underlying data structures has been steadily increasing. In this article we introduce an approach of how to ensure consistency within car manufacturing data with the help of a Multi-Valued Decision Diagram (MDD). The data basis of the car manufacturing application is not derived from higher level models and therefore lacks structural information. For large real world applications, the corresponding MDD cannot be constructed due to memory limitations even if well-known dynamic variable reordering techniques are used. Therefore, a combination of three dynamic variable reordering approaches and the sorting of the sequence of data compilation are introduced. Using this algorithm, the decision diagram can now be constructed with a low memory consumption in reasonable time. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD7.mddbas
Keywords: car manufacturing; multi-valued decision diagram; product configuration; variable ordering; verification

Multi-Valued Decision Diagrams for the Verification of Consistency in Automotive Product Data - Berndt, Rüdiger; Bazan, Peter; Hielscher, Kai-Steffen; German, Reinhard; Lukasiewycz, Martin (Proceedings of 12th International Conference on Quality Software (IEEE), 2012)
Highly customizable products and mass customization - as increasing trends of the last years - are mainly responsible for an immense growth of complexity within the digital representations of knowledge of car manufacturers. We developed a method to detect and analyze inconsistencies by employing a Multi-Valued Decision Diagram (MDD) which is used to encode the set of all valid product configurations. On this basis, we stated a number of rules of consistency that are checked by a set-based verification scheme. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD7.multiv
Keywords: Digital manufacturing; Formal verification; Knowledge representation; Multi-valued decision diagram; Product configuration

On the Ordering of Variables of Multi-Valued Decision Diagrams - Berndt, Rüdiger; Bazan, Peter; Hielscher, Kai-Steffen (Leistungs-, Zuverlässigkeits- und Verlässlichkeitsbewertung von Kommunikationsnetzen und Verteilten Systemen, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD7.ontheo

Precompiled Configuration Spaces for the Verification of Consistency in Production Planning Processes - Berndt, Rüdiger; Bazan, Peter; Hielscher, Kai-Steffen (25th European Conference on Operational Research, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD7.precom

Product Line Fault Tree Analysis by Means of Multi-valued Decision Diagrams - Käßmeyer, Michael; Berndt, Rüdiger; Bazan, Peter; German, Reinhard (Measurement, Modelling and Evaluation of Dependable Computer and Communication Systems. MMB&DFT 2016. Lecture Notes in Computer Science, vol 9629., 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.IMMD.IMMD7.produc

Schlanke Informationsflüsse für eine effiziente Produktion - Risch, Florian; Berndt, Rüdiger; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IMMD.IMMD7.schlan

Toward an MDD-based Analysis of Stateful and Variant-rich Automotive Functions - Käßmeyer, Michael; Berndt, Rüdiger; Bazan, Peter; German, Reinhard (CARS 2016-4th International Workshop on Critical Automotive Applications: Robustness & Safety, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD7.toward_7

Towards High-Quality Automotive Product Configuration Data using Meta-Rules - Berndt, Rüdiger; Ziterell, Dirk (Proceedings of the 17th International Conference on Information Quality, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD7.toward_2

Towards the City-scale Simulation and Performance Assessment of Electric Vehicles - Masalkina, Ekaterina; Eckhoff, David; Berndt, Rüdiger; German, Reinhard (2nd GI/ITG KuVS Fachgespräch Inter-Vehicle Communication (FG-IVC 2014), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.toward
Keywords: non-peer

Worst Case Modeling of Aggregate Scheduling by Network Calculus - Klehmet, Ulrich; Berndt, Rüdiger (Proceedings, 2015)
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD7.worstc